(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the 1920s, the Uzbek language was published in 1919 by Chigotay Gurugi as a work reflecting the rules of the Uzbek language. We can show such works as "Sarf" (Morphology) and "Nahv" (Syntax), "Rules of Uzbek language" written by M.Qori, Q.Ramazon, Sh.Zunnun for primary schools in 1925.The category of horse (noun) is first mentioned in the "Ways of Agreement" and the term is used in all organized sources. Only Abdurauf Fitratgina used it as a horse in his 1927 work Sarf, which later gave rise to the term. This term has an important place in Uzbek linguistics. The term name is still found in some works.